(untitled) (Experimental biology, 2015)
The objective of this study was to evaluate and compare quality characteristics of Infraspinatus (IS), Triceps brachii (TB), Longissimus thoraces (LT), Biceps femoris (BF), Semitendinosus (ST), and Semimembranosus (SM) muscles from nine Bactrian camel carcasses. Individual muscles were collected to measure color, expressed juice, cooking loss, pH, sarcomere length, shear force value, myofi brillar fragmentation index. The pH for the six muscles was monitored at 1, 2, 4, 8, 12, 24 and 48 hrs postmortem. The TB muscle had a signifi cantly (P